Case report of caesarean related scar endometriosis and literature review - A.S., Dayang Nurul Afifah; Abd Malik, Nur Rashidah; M.R., Nurul Nafizah; Ismail, Hamizah; Hamdan, Asmah Hanim (Universiti Kebangsaan Malaysia, 2023)
Introduction: Caesarean related surgical scar endometriosis is a type of extremely rare abdominal wall endometriosis. Slow growing, chronic pain with increasing severity, the women often suffer in silence. Given the latency of symptoms from initial surgery, presentations or referrals are often to others than obstetricians. We present a case of Caesarean scar endometriosis referred from surgical department. Case Report: A 43 years old, multiparous lady with last child birth via Caesarean section 10 years prior, presented to surgical department with right inguinal mass. She also reported presence on painful lump over the left edge of her Pfannenstiel scar for past 10 years, some months after her Caesarean section. She has been having chronic cyclical pain and palpable lump during her menses which only became increasingly severe more recently. Examination revealed normal skin colour with palpable 2x3 cm hard nodular swelling with irregular border beneath the left edge of Pfannenstiel scar. Ultrasonography revealed subcutaneous nodule measuring 2.5x 2.7 cm with similar echogenicity to the endometrial lining. Surgical excision of the swelling was performed concurrently with surgery for the huge right inguinal mass (lipoma). Histopathologic examination (HPE) findings of the scar mass confirmed the initial diagnosis of scar endometriosis. Discussion: Caesarean section poses highest risk for development of surgical scar endometriosis. Cyclical pain related to menses is highly suggestive of endometriosis. Presence of previous abdominal surgery especially Caesarean section along with pain and subsequent mass should raise the suspicion. Treatment with surgical excision is highly curative with ability to confirm diagnosis through HPE. Nevertheless, prevention is better than cure. Suggested surgical practice is to avoid using the same needle and suture used in uterine closure for rectus and subcutaneous suturing and cleaning of subcutaneous area post rectus closure may reduce the occurrences of scar endometriosis.